2021
DOI: 10.52462/jlls.49
|View full text |Cite
|
Sign up to set email alerts
|

The English Google translation of Indonesian lecturer’s academic writing: A preliminary study

Abstract: The work of translation seems to be much easier with the assistance of web-based Machine Translation such as Google Translate. Does it work well? This study aims at finding how Google translates academic texts from Indonesian into English. It is also to find the extent to which Google Translate accurately and naturally transfers such texts. The data are Indonesian academic texts written by undergraduate lecturers from three different majors: Management, Japanese Literature, and Mathematics. The discussion sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…In terms of frequency of use of GT by the students, the data indicated that more than half of the students (54.67%) reported using GT often, and less than half of them stated that they use it sometimes. In agreement with the present study, Winiharti et al (2021) found that more than half of the participants (56%) used GT often, whereas almost a quarter (21.33%) used it sometimes. The results also concur with Alharbi (2022), who discovered that Saudi EFL students frequently used GT while learning English.…”
Section: Discussionsupporting
confidence: 93%
“…In terms of frequency of use of GT by the students, the data indicated that more than half of the students (54.67%) reported using GT often, and less than half of them stated that they use it sometimes. In agreement with the present study, Winiharti et al (2021) found that more than half of the participants (56%) used GT often, whereas almost a quarter (21.33%) used it sometimes. The results also concur with Alharbi (2022), who discovered that Saudi EFL students frequently used GT while learning English.…”
Section: Discussionsupporting
confidence: 93%
“…In another academic situation, like editing, Zhang and Torres-Hostench (2022) also added that tools like Google Translate is employed by the students. More daily activities, like generating and checking captions in social media, Google Translate is also possible (Murtisari et al, 2019;Sutrisno, 2020) due to benefits it provided in the target language (Winiharti et al, 2021). These studies show that situations, both formal and informal, provided assistance to the students to employ supporting tools, like Google Translate to assist their performances.…”
Section: Discussionmentioning
confidence: 89%
“…Membawa cahaya ke genre tersembunyi: laporan tinjauan sejawat diteliti oleh Mason (2022). Terjemahan Google bahasa Inggris dari tulisan akademik dosen bahasa Indonesia: Studi pendahuluan diteliti oleh Winiharti (2021).…”
unclassified